Involving adolescents with intellectual disability in the adaptation of self‐reported subjective well‐being measures: participatory research and methodological considerations. Issue 7 (6th May 2022) - Davison, J.; Maguire, S.; McLaughlin, M.; Simms, V.
Abstract: Background: The measurement of subjective well‐being is challenging with samples of adolescents with intellectual disability (ID) given the cognitive and linguistic difficulties they face in comprehending standardised measures, and as such is primarily based on proxy reports. The lack of appropriate tools needs to be addressed so that adolescents with ID can self‐report on their own well‐being. The current study reports on the use of participatory research methods to adapt and modify two standardised self‐report measures of subjective well‐being suitable for completion by adolescents with ID. Method: Two special schools were recruited for this study. At each school, staff ( n  = 15) and pupils aged 11–17 years ( n  = 35) participated. A series of co‐design workshops were conducted to adapt two standardised subjective well‐being measures: Kidscreen‐10 and short‐form Warwick–Edinburgh Mental Well‐being Scale. Results: Specific aspects for measure adaption were identified: simplifying the item wording and phrasing; inclusion of pictorial communication symbols and visual prompts to represent the meaning of items; changing of tense of questions from past to present; asking questions rather than statements; reducing 5‐point Likert scales to 3‐point or dichotomous; presenting one item at a time during administration; and developing alternate formats of the survey to ensure inclusivity. Conclusions: This paper illustrates the value of using participatory research methods when working alongside adolescents with ID and offers methodological, as well as practical, guidance in the context of adapting subjective self‐report measures for this target group, serving as a guide to fellow researchers and clinicians interested in modifying or developing self‐report measures for adolescents with ID.